Strategies for Integrating Religious Moderation Values in Islamic Higher Education - A. Syathori; Umamatul Khaeriyah (Journal La Edusci, 2026)
This study examines strategies for instilling religious moderation values in enhancing Islamic Religious Education within the Department of Islamic Education at UIN Siber Syekh Nurjati Cirebon. Employing a qualitative case study approach, the research investigates how religious moderation is integrated into the curriculum, pedagogical practices, and academic culture of an Islamic higher education institution operating in a digital learning environment. Data were collected through in-depth interviews with lecturers, students, and academic administrators, classroom observations, and analysis of curriculum documents and institutional policies. The findings reveal that religious moderation is systematically embedded across core courses through dialogical teaching, experiential learning, interfaith dialogue, and community engagement. These strategies contribute to the development of students’ moderate religious attitudes, critical thinking skills, and social inclusivity. However, the study also identifies challenges related to student resistance, uneven faculty preparedness, and the influence of digital media in shaping religious perspectives. The study concludes that sustained institutional commitment, faculty development, and adaptive curriculum design are essential for strengthening religious moderation education in Islamic higher education. This research contributes to the discourse on Islamic education by offering an integrative model for promoting religious moderation in pluralistic and digital contexts.